Amygdala lesions in rhesus macaques decrease attention to threat - Dal Monte, Olga (Nat Commun, 2015)
Evidence from animal and human studies has suggested that the amygdala plays a role in detecting threat and in directing attention to the eyes. Nevertheless, there has been no systematic investigation of whether the amygdala specifically facilitates attention to the eyes or whether other features can also drive attention via amygdala processing. The goal of the present study was to examine the effects of amygdala lesions in rhesus monkeys on attentional capture by specific facial features, as well as gaze patterns and changes in pupil dilation during free viewing. Here we show reduced attentional capture by threat stimuli, specifically the mouth, and reduced exploration of the eyes in free viewing in monkeys with amygdala lesions. Our findings support a role for the amygdala in detecting threat signals and in directing attention to the eye region of faces when freely viewing different expressions.